Pengaruh Web Tarantula Sebagai Filler Bio Komposit Pada Pengujian Impak - Barkah, Imam Subarkah; Yuliyanto, Yuliyanto; Haritsah Amrullah, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
During this time animal fibers were often used only for textile products, from the mechanical properties of the Tarantula Web that were already known, the idea arose to utilize the Web Tarantula as a composite reinforcement. Composites will not form if they only use reinforcement, it is necessary to have a mixture of matrices so that the composite can blend perfectly. This study will use a Hollow Glass Microsphere (HGM) & Epoxy matrix. The printing process is carried out in layers, the first layer pours the homogeneous half of HGM-Epoxy on the mold until it covers the base of the mold, then assembles the weighed web into the mold, and finally pours back the remaining HGM-Epoxy until it fills the mold. The tested specimen data was then processed using Microsoft Excel to determine the effect of volume fraction on the impact strength of the Web Tarantula composite with HGM-Epoxy homogeneous matrix. The conclusion in this study is, Web Tarantula fillers 10%, 20%, and 30% do not greatly affect the homogeneous mechanical strength of HGM-Epoxy 20%/80% and 30%/70%, from six specimens with different volume fractions, after impact testing using the Charpy impact method, the five composites have the same value, only one specimen with Web 30%, HGM 30%, and Epoxy 70% has slightly different values. It can be concluded that the volume fraction of Web Tarantula, Homogeneous HGM-Epoxy does not add impact strength to the specimen made.